Perceptions and Attitudes of the Local Community towards Urban Refugees Living in Mbarara City, Southwestern Uganda: A Cross-Sectional Study. - Bahati, Ronald; Rukundo, Godfrey Zari; Sigmund, Cathy Denise; Ainamani, Herbert Elvis; Ashaba, Scholastic (Student’s Journal of Health Research Africa, 2022)
Background: There is an increasing number of refugees choosing to live in urban centers even when this makes them forego humanitarian assistance such as shelter and food from the United Nations High Commission for Refugees (UNHCR) and host governments. Refugees in urban centers have to fend for themselves. This situation sometimes makes them ‘lock horns’ with the local communities. We examined the perception of the local community towards urban refugees in Mbarara city southwestern Uganda. Methods: We conducted 6 Focus Group Discussions composed of local leaders of the villages where refugees live. We also conducted 4 Key Informants Interviews with the Refugee Desk Officer (Office of The Prime Minister), the Officer in Charge of Mbarara Police Station, the Mayor Mbarara city, and the Resident City Commissioner. All participants were purposively selected due to their knowledge about the study topic. They were interviewed about their perceptions towards refugees in Mbarara city. All interviews were audio-recorded, transcribed verbatim, and thematically analyzed. Results: Three themes emerged from the data: 1) Economic perceptions (employment competition, competition for land, basic needs scarcity, skilled labor, and economic favoritism) 2) Political perceptions (corruption, involvement in local politics, and security threat) 3) Sociocultural perceptions (religiosity, cultural acculturation, social inclusion, stigma, and sexual immorality) of society towards urban refugees. Conclusions: The community views refugees as people who are given preferential treatment by the government, civil society organizations, and the international community. Recommendation: Integration interventions are designed to ensure peaceful and cordial coexistence between the host community and refugees for sustainable development.